Artificial incubation of ostrich eggs (Struthio camelus), on the northeast coast of Brazil (Research, Society and Development, 2025)
This study aimed to evaluate data collected on ostrich eggs in a commercial hatchery, focusing on physical characteristics, incubation temperature, relative humidity inside the incubator, egg fertility, embryonic mortality, egg mass at collection, mass loss during artificial incubation, chick mass at hatching, shell weight, and hatching rate. The eggs were cleaned with paper towels, individually identified, and weighed at collection and subsequently on days 14, 28, and 39 of incubation. Prior to incubation, the eggs were stored for four days at 18–20 °C and 50–60% relative humidity. Incubation was carried out at 36–37 °C and 25–35% relative humidity. Candling was performed at the beginning of incubation and on days 14, 28, and 39 to assess embryonic development. At hatching, both chicks and eggshells were weighed. Of the 120 eggs, 101 were fertile (84.16%) and 19 (15.83%) infertile; among the fertile eggs, 14 (13.86%) resulted in embryonic mortality. A total of 87 chicks hatched, corresponding to a hatchability rate of 86.13% among fertile eggs. The mean initial egg mass was 1,308.78 ± 157.08 g, and the mean chick mass at hatching was 815.56 ± 129.23 g, representing 61.13% of the initial egg mass. The mean egg mass loss during incubation was 19.97 ± 5.18%, a value higher than those reported in previous studies.